Stroke Update: An Overview of What is Going on in the Area of Stroke - Nierengarten, Mary Beth (MD Conference Express, 2013)
During an invited symposium at the 2013 International Stroke Conference, investigators shared their thoughts on key areas in stroke research that will shape the field in a number of ways. Topics include: an epidemiological look at stroke mortality and its global health burden, a review of the current state of clinical trial research, a discussion of the need for the recognition of and attention to vascular cognitive impairment, and the current and future need for drugs and devices for restorative therapy after stroke, among other things.